2017
DOI: 10.1039/c7nr02115a
|View full text |Cite
|
Sign up to set email alerts
|

Realisation and optical engineering of linear variable bandpass filters in nanoporous anodic alumina photonic crystals

Abstract: We present the first realisation of linear variable bandpass filters in nanoporous anodic alumina (NAA-LVBPFs) photonic crystal structures. NAA gradient-index filters (NAA-GIFs) are produced by sinusoidal pulse anodisation and used as photonic crystal platforms to generate NAA-LVBPFs. The anodisation period of NAA-GIFs is modified from 650 to 850 s to systematically tune the characteristic photonic stopband of these photonic crystals across the UV-visible-NIR spectrum. Then, the nanoporous structure of NAA-GIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…4 NAA-PCs have distinctive PSBs, the features of which can be readily tuned across the spectral regions by engineering the effective medium of NAA in a multi-dimensional fashion, through various anodization approaches. 45,[47][48][49][50][51][52] These NAA-PC platforms include optical microcavities 47,48 , distributed Bragg reflectors 5 (DBR) 45,49 , linear variable bandpass filters 50 , gradient-index filters 51 , and hybrid PCs 52 . These PC structures provide new opportunities to rationally utilize the "slow photon" effect to attain an efficient management of photons at the nanoscale for photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…4 NAA-PCs have distinctive PSBs, the features of which can be readily tuned across the spectral regions by engineering the effective medium of NAA in a multi-dimensional fashion, through various anodization approaches. 45,[47][48][49][50][51][52] These NAA-PC platforms include optical microcavities 47,48 , distributed Bragg reflectors 5 (DBR) 45,49 , linear variable bandpass filters 50 , gradient-index filters 51 , and hybrid PCs 52 . These PC structures provide new opportunities to rationally utilize the "slow photon" effect to attain an efficient management of photons at the nanoscale for photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…This top-down nanofabrication approach offers industrial scalability (from mm 2 to m 2 ), cost-competitiveness, and versatile control over the features of nanopores, which can be modulated with precision by means of the anodization parameters to generate unique multi-dimensional PC structures able to guide, reflect, modulate, confine, transmit, emit, and enhance incident light selectively across the spectral regions 17 , 18 . Recent studies have demonstrated that rationally designed pulse-like anodization profiles under suitable conditions enable the precise engineering of the photonic stopband (PSB) of NAA-PCs by creating structures such as gradient index filters 19 22 , optical microcavities 23 , distributed Bragg reflectors 24 – 28 , bandpass and linear variable bandpass filters 29 , 30 . These PCs can be used as optical filters for a plethora of applications due to the flexibility and selectively to engineer their light-filtering features across the spectral regions 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…NAA-LVBPFs have a PSB with variable central wavelength, the position of which is shifted across the surface of the filter in a linear fashion. This effect is achieved by a selective etching of the nanoporous structure of NAA-LVBPFs to engineer their effective medium in the perpendicular direction to the nanopores’ growth [ 87 ].…”
Section: Fabrication and Properties: Nanoporous Anodic Alumina As mentioning
confidence: 99%
“…Different forms of NAA-PCs (e.g., distributed Bragg reflectors, grading-index filters, optical microcavities, Fabry–Pérot interferometers, etc.) can be integrated with various optical techniques such as reflectometric interference spectroscopy (RIfS), reflection and transmission spectroscopy, and photoluminescence spectroscopy (PL) ( Table 2 ) [ 29 , 87 , 230 ]. This section summarizes the most representative examples of chemo- and biosensing systems combining NAA-PC structures with optical techniques.…”
Section: Nanoporous Anodic Alumina Photonic Crystals As Optical Sementioning
confidence: 99%